RELATIONSHIP MANAGEMENT DALAM E-COMMERCE BUTIK GRIYA GAYA - Harimurti, R.M. Agung; Wuragil, Astri (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2014)
CRM (Customer Relationship Management) is a marketing strategy to create and maintain a good relationship with the customer and reduce the likelihood of customers switching to a competitors product. this study aims to analyzes the requirements of design based on CRM in Griya Gaya using PHP as programming language and MySQL data base for storing data. The results obtained are e-Commerce applications based CRM to manag ecustomer data, product promotion, product demand data, and management of discussion forums that are used to accommodate customer inquiries and complaints in order to create a good relationship with the customer. The implementation of these applications are expected to maintain good relationships with customers and gain new customers, which ultimately brings benefits for the company.